2009
DOI: 10.1590/s0100-879x2009000400008
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus delbrueckii UFV-H2b20 induces type 1 cytokine production by mouse cells in vitro and in vivo

Abstract: Lactobacillus delbrueckii UFV-H2b20 has been shown to increase clearance of bacteria injected into the blood of germ-free mice. Moreover, it induces the production of type 1 cytokines by human peripheral mononuclear cells. The objective of the present study was to investigate the production of inflammatory cytokines [interleukin-12 (IL-12 p40), tumor necrosis factor-α (TNF-α), and interferon-γ (IFN-γ)] triggered in vitro by live, heat-killed or lysozyme-treated L. delbrueckii UFV-H2b20 and in vivo by a live pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The next step was to verify the mechanisms by which L. delbrueckii UFV-H2b20 regulates the immune response during infection. Previous studies by our group showed that L. delbrueckii UFV-H2b20 modulates host cytokine production [21][22][23]. Therefore, we veri ed the pro le of in ammatory mediators in the airways.…”
Section: Lactobacillus Delbrueckii Ufv-h2b20 Intake Promotes Regulati...mentioning
confidence: 70%
See 1 more Smart Citation
“…The next step was to verify the mechanisms by which L. delbrueckii UFV-H2b20 regulates the immune response during infection. Previous studies by our group showed that L. delbrueckii UFV-H2b20 modulates host cytokine production [21][22][23]. Therefore, we veri ed the pro le of in ammatory mediators in the airways.…”
Section: Lactobacillus Delbrueckii Ufv-h2b20 Intake Promotes Regulati...mentioning
confidence: 70%
“…Lactobacillus delbrueckii UFV-H2b20 is a typical intestinal tract inhabitant probiotic [20]. Studies from our group have already shown L. delbrueckii UFV-H2b20 ability to stimulate their host immune system by enhancing phagocytic capacity by macrophages and improving gram-negative bacteria elimination [20,21], inducing in ammatory cytokine production in vitro and in vivo [22,23]. Here, we demonstrate that oral administration of L. delbrueckii UFV H2b20 can protect mice against A. fumigatus lung infection by increasing cytokine production and numbers of cells involved in immune regulation and improving mechanisms of fungal clearance.…”
Section: Introductionmentioning
confidence: 99%
“…Ishida-Fujii et al [24] reported that peritoneal macrophages from rats fed with Lactobacillus casei and intraperitoneally infected with E. coli had improved phagocytic activity and produced higher quantities of TNF-a. Previous studies from our group showed that L. delbrueckii UFV-H2b20 stimulates production of cytokines by mouse and human cells in vitro [25,26]. Here, L. delbrueckii UFV-H2b20 triggered the in vivo production of TNF-a and IFN-c, cytokines that mediate the resistance to L. monocytogenes infection.…”
mentioning
confidence: 77%
“…6,7) Neumann et al reported that interleukin-12 (IL-12) or interferongamma (IFN-γ) production from mouse peritoneal cells or splenocytes was equally induced by live Lactobacillus delbrueckii and dead bacteria. 8) Recently, Adams reported that the use of dead probiotics as biological response modifiers has several attractive advantages compared to live probiotics. 9) Ueno et al reported that heat-killed bacteria could maintain intestinal homeostasis and improve intestinal disorders without the need for live probiotics.…”
Section: Introductionmentioning
confidence: 99%